Biology of Silverbelly, Photopectoralis bindus (Val. 1835) along Ratnagiri Coast - Borah, B. S.; Nirmale, V. H.; Metar, S. Y.; Bhosale, B. P.; Chogale, N. D.; Pawar, R. A. (Fishery Technology, 2016)
Food and feeding habits, reproduction and size at first maturity of Photopectoralis bindus from Ratnagiri coast are described, based on commercial catches landed by trawls during 2013-2014. Copepods, diatoms and cladocera form important food of the species. The estimated length at first maturity is 93.5 mm. P. bindus is a fractional spawner and appears to release the ova in at least two spawning acts during the peak spawning season extending from October to December. High gonado-somatic indices correspond well with the peak spawning seasons and females always have higher values. The estimated fecundity ranged from 4377 to 10 449.